Potensi Pemanenan Air Hujan Untuk Kebutuhan Air Non Domestik pada Peternakan Ayam Petelur di Jati Agung, Lampung Selatan - Adinata, Chandra; Zain, Alfath; Yacub, Vanita Kesumawati (Universitas Batanghari Jambi, 2025)
Mas Kus Layer Chicken Farm uses groundwater to meet its clean water needs. There is not enough groundwater on this farm to meet all clean water demands. To increase the availability of clean water, a Rainwater Harvesting (PAH) system was installed as a backup plan and an effort to use natural resources. A hydrological approach was used to analyze the maximum daily rainfall, which was then used to collect rainwater. This study used a quantitative descriptive methodology, and the rainfall of Mas Kus Layer Chicken Farm, the roof area of the building, the capacity of the reservoir, and the need for clean water provided supporting data. The results of the analysis showed that the potential for rainwater harvesting could meet up to 99% of the total clean water needs at Mas Kus Layer Chicken Farm. The storage system used is a Ground water Tank measuring 10x10x2.26 m. With this capacity, the rainwater that can be collected reaches 7,530 liters/day or 7.53 m3/day so that in one month it can accommodate around 226 m3/month.